Expression profiling of genes related to endothelial cell function in pre-diabetes and type 2 diabetes subjects - Moradipoor, Sara (2016)
Type 2 diabetes mellitus (DM2) is a major chronic disease with high morbidity, mortality, and economic burden on public health. The term “endothelial dysfunction” refers to the inability of the endothelium to properly maintain vascular homeostasis. Substantial clinical and experimental evidence suggests that endothelial dysfunction occurs in T2DM patient, in both the resistance and conduit vessels of the peripheral circulation as well as in the coronary circulation. Endothelial dysfunction could be the mechanism in explaining the strong association observed between atherosclerotic cardiovascular disease (CVD) and type 2 diabetes mellitus. It has also been shown that patients with prediabetic conditions, such as impaired fasting glucose and impaired glucose tolerance, are at increased risk of cardiovascular disease as well. The first step of the adverse sequence of events that leads to the atherosclerotic process is thought to be endothelial dysfunction. Many genes have already been reported to be related to endothelial dysfunction in type 2 diabetes and prediabetic patients [e.g. endothelial nitric oxide synthase (eNOS) ], but the identification of more genes is always a field of further investigation because of the potential finding of new targets for prevention of CVD in type 2 diabetes patients. The aim of this study was to evaluate the expression of a set of genes in peripheral blood associated with endothelial dysfunction in patients with type 2 diabetes mellitus and in those with impaired fasting glycaemia and impaired glucose tolerance (prediabetic patients), trying to find out the relationship between expression of this set of genes and these two pathological conditions. 45 subjects (22 men, 23 women), with a mean age of 48.9 ±5.71 years, were included in the study. We have recruited the participants after evaluation of fasting glucose and glucose tolerance and HbA1c. According to the results of fasting glucose, glucose tolerance and HbA1c, the participants were divided into three age-matched groups: group 1: diabetes, defined as fasting plasma glucose ≥ 126mg/dl or 2–h plasma glucose ≥ 200mg/dl and HbA1c ≥6.5 (n=15), group 2: Pre-diabetes, defined as fasting plasma glucose between 110 to 125 mg/dL or IGT 2h post-oral glucose load (75g) between 140mg/dl and 200mg/d and HbA1c between 5.7% to 6.4% (n=15), and group 3 (control group): healthy individuals with normal fasting plasma glucose and normal glucose tolerance (n=15). In patients with type 2 diabetes, we found 59 genes with increased expression. Decreased expression was observed for 4 genes. In pre-diabetes patients, 2 genes were seen to be significantly down-regulated and 49 genes were significantly up-regulated. Our results indicate that diabetic and pre-diabetic condition may contribute to endothelial dysfunction by disrupting the expression of genes involved in the regulation of endothelial function.